Exploration of the associations between muscle oxygen saturation and skin temperature responses during isokinetic strength exercise - Willian da Silva; Carlos Sendra-Pérez; Joaquín Martín Marzano-Felisatti; Inmaculada Aparicio-Aparicio; Felipe P. Carpes; Jose Ignacio Priego-Quesada (PLoS ONE, 2026)
Previous studies suggested that skin blood flow, and therefore skin temperature affect changes in muscle oxygenation (SmO 2 ). Given that near-infrared spectroscopy (NIRS) measurements consider a depth of a few centimeters to capture changes in SmO 2 , in this study, we aimed to explore whether a relationship between skin temperature and SmO 2 is observed after sets of isokinetic strength exercises. Seventeen males (age: 25 ± 6 years old and body mass: 74.7 ± 12.4 kg) completed five series of 30 maximum unilateral (preferred) knee extension isokinetic exercises at 180º·sec -1 with a 60-second rest between series to exercise quadriceps muscles. At baseline, after a warm-up, and 50 seconds after each series of exercise, SmO 2 related to vastus lateralis and skin temperature of the anterior thigh were evaluated in the exercised and non-exercised legs. Significance was established at p < 0.05. Exercise reduced mean skin temperature throughout the consecutive repetitions in both the exercised and non-exercised legs (p < 0.01). SmO 2 increased during exercise only in the exercised leg. No significant correlations were found between skin temperature and SmO 2 , and weak correlations were observed between skin temperature and total haemoglobin for absolute (r = 0.4 and p < 0.001) and delta values (r = 0.3 and p = 0.03) only in the non-exercised leg. In conclusion, this exploratory study suggests that skin temperature and SmO 2 are compatible as they explain different physiological responses, although these measurements are not associated during a controlled exercise.